Perkembangan Ekonomi Islam Berdasarkan Sejarah , Budaya , Sosial dan Keagamaan di Indonesia - Idris Parakkassi (Tekstual, 2018)
The economic system of Islam is an integral part of Islamic law that a complete and universal.Aiming to achieve prosperity and happiness of human life in this world and hereafter (Falah).The development of the economic system of Islam in Indonesia along with the entry process andthe development of Islamic law in Indonesia. The process of entry and the development of theeconomic system of Islam in Indonesia strongly supported and influenced the social conditions,culture, community activities and religious system adopted by the people of Indonesia. Islamarrived in Indonesia with trade missions and preaching greatly facilitate the acceptance andimplementation of the economic system of Islam in Indonesia, where most of the kingdoms inIndonesia is located in the coastal areas which most economic activity is trade. The collapse ofthe kingdom of Srivijaya and Majapahit kingdoms rose and encourage the formation of theIslamic empire in many coastal areas in Indonesia. So that the establishment of the Islamicempire that begins with propaganda, acculturation with the local culture as well as interaction intrade accelerates economic growth and development of Islam in Indonesia. The role of Islam inIndonesia economic power affects people very vital for the fight against colonialism, the nationalmovement, the formation of the country's economic, scientific studies and Islamic institutionalstrengthening economy.